Effectiveness of Interpersonal Communication of Employees in the Department of Communication, Informatics, Statistics and Coding of Gowa District - Said, Nurannisa Yahya; Sirajuddin Saleh; Isgunandar (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
The effectiveness of employee interpersonal communication is the ability of employees to communicate in a way that can improve understanding and avoid misunderstandings. This study aims to determine employee interpersonal communication and identify supporting and inhibiting factors in employee interpersonal communication at the Gowa Regency Communication, Informatics, Statistics, and Cryptography Service. This research approach is a qualitative research approach and a descriptive type of research. Data collection techniques used in this study were observation, interviews, and documentation methods. The data analysis techniques used were data reduction, data presentation, conclusions, and verification techniques. The results of this study indicate that all indicators used in the study of employee interpersonal communication effectiveness at the Gowa Regency Communication, Informatics, Statistics, and Cryptography Service are classified as effective. This is evidenced by the trust indicator being classified as effective because the relationship between employees in an office is based on mutual trust and shared perceptions among other employees. The honesty indicator is classified as effective because employees demonstrate honest attitudes and behaviors by providing true and accurate information to coworkers. The supportive attitude indicator is classified as effective because there is a caring attitude for all parties that can be felt by providing motivation. The open attitude indicator is classified as effective because the delivery of information is conveyed clearly and states the actual situation openly. This study presents new information by linking detailed theories and different research loci from previous studies regarding the effectiveness of employee interpersonal communication so that it can be used as evaluation material for research loci to improve the quality of employee interpersonal communication.